2007
DOI: 10.1182/blood.v110.11.4742.4742
|View full text |Cite
|
Sign up to set email alerts
|

Early Reduction of Serum Free Light Chain Can Predict Therapeutic Responses in Multiple Myeloma.

Abstract: Background M protein as measured by serum protein electrophoresis (SPE) is usually required for the diagnosis and therapeutic monitoring of multiple myeloma. However, SPE may not be able to detect M protein in some cases such as light-chain disease or non-secretory myeloma. Serum free light chain (FLC) assay has been recently developed and shown to be very helpful in such situations. Here, we evaluate the usefulness of this new test in the diagnosis and therapeutic monitoring of myeloma patients treated with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On multivariate analysis, post‐transplantation sCR was an independent prognostic factor for survival (hazard ratio, 0·44; 95% confidence interval, 0·25 to 0·80; versus CR; P = 0·008). Several other studies have shown independent prognostic value of normalization of sFLC ratios (Tacchetti et al , )(Iwama et al , )(Cavallo et al , )(Nakorn et al , )(Watanboonyongcharoen et al , ). However, a recent publication by PETHEMA (Programa para el Estudio de la Terapéutica en Hemopatías Malignas) group (Martínez‐López et al , ) has questioned the prognostic value of normalization of sFLC.…”
Section: Discussionmentioning
confidence: 91%
“…On multivariate analysis, post‐transplantation sCR was an independent prognostic factor for survival (hazard ratio, 0·44; 95% confidence interval, 0·25 to 0·80; versus CR; P = 0·008). Several other studies have shown independent prognostic value of normalization of sFLC ratios (Tacchetti et al , )(Iwama et al , )(Cavallo et al , )(Nakorn et al , )(Watanboonyongcharoen et al , ). However, a recent publication by PETHEMA (Programa para el Estudio de la Terapéutica en Hemopatías Malignas) group (Martínez‐López et al , ) has questioned the prognostic value of normalization of sFLC.…”
Section: Discussionmentioning
confidence: 91%